Oblikovanje dirkalnika - Pehan, Stanislav (Strojniški vestnik, 2003)
This article presents two approaches for improving a Formula S racing car. Oneof the best ways to increase the enginećs power is to skillfully design theair- supply system of the engine. This is the reason why the first part of the paper is about the intake-manifold optimization procedure. The procedure relies on mathematical programming and offers a way to significantly increase the engine power in the most important engine regimes. In the second part of the paper, attention is focused on new concepts of building the racing car. Inorder to be the best it is necessary to do more than symply follow the competion. An analysis of the positions of the main components has shown that a racing car would be more agile and stable if the engine was to be mounted beside the driver. Optimizing the intake manifold represents one significant step forward in the struggle to increase the effective power of the car, whichbrings an immediate advantage. The new position concept, however, which also eliminates the differential drive, represents a completely new development in the design of the Formula S car that might bring us long-term benefits.
Keywords: dirkalni avtomobili; formula S; razvoj; optimiranje; sistemi sesalni; konstruiranje